Islamic corporate governance, profitabilitas, leverage, dan nilai perusahaan: Peran moderasi ukuran perusahaan - Rositaningrum, Vinna Agustin; Soleh, Mohammad (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2024)
This research aimed to analyze the influence of Islamic corporate governance, profitability and leverage on company value with company size as a moderating variable in manufacturing companies listed on the BEI in the food and beverage sector for the 2018-2022 period. This research uses a quantitative type of research using regression analysis as data analysis. The research uses secondary data in panel form using annual report data for 2018-2022. This research shows that the variables of Islamic corporate governance, profitability and leverage, moderated by company size, simultaneously influence company value. In contrast, Islamic corporate governance and profitability significantly positively affect company value. Company size can moderate Islamic corporate governance on company value, while size cannot moderate profitability and leverage.